2013
DOI: 10.1177/0363546513484696
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Outcome 5 Years After Matrix-Induced Autologous Chondrocyte Implantation in the Tibiofemoral Joint

Abstract: This study outlined factors such as preoperative SF-36 scores, duration of knee symptoms, graft size, and postoperative course of weightbearing rehabilitation as pertinent variables involved in 5-year clinical and radiological outcomes and overall satisfaction. This information may allow orthopaedic surgeons to better screen their patients as good candidates for MACI, while allowing treating therapists to better individualize their preoperative preparatory and postoperative rehabilitation regimens for a best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 77 publications
(156 reference statements)
2
43
1
Order By: Relevance
“…Ultimately, the determination of what factors are predictive of clinical outcome following cartilage repair will be multivariate, considering the numerous patient-specific and cartilage lesion–specific variables. Patient age, 31 , 50 , 55 , 56 BMI, 32 , 57 time from onset of symptoms, 34 , 56 gender, lesion size, and location are all relevant, 58 although other procedure-based parameters such as technical aspects of the surgical treatment and postoperative rehabilitation 58 , 59 could also play critical roles. Consequently, the correlation between repair tissue structure and clinical outcomes has been elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the determination of what factors are predictive of clinical outcome following cartilage repair will be multivariate, considering the numerous patient-specific and cartilage lesion–specific variables. Patient age, 31 , 50 , 55 , 56 BMI, 32 , 57 time from onset of symptoms, 34 , 56 gender, lesion size, and location are all relevant, 58 although other procedure-based parameters such as technical aspects of the surgical treatment and postoperative rehabilitation 58 , 59 could also play critical roles. Consequently, the correlation between repair tissue structure and clinical outcomes has been elusive.…”
Section: Discussionmentioning
confidence: 99%
“… 50 , 56 , 60 , 61 A recent cohort study following MACI treatment used multivariate models to assess predictive factors, including a subjective MRI composite score, but no correlation with KOOS (Knee injury and Osteoarthritis Outcome Score) sports/recreation or SF-36 was identified. 58 Reviews of the topic agree that there are major inconsistencies between MRI structural outcomes, repair procedures, and their resulting clinical benefits, 62 , 63 and that analysis of longer term studies are complicated by the potential for progression of degenerative changes in the knee or new unrelated knee pathology. Previous studies have been limited to subjective semiquantitative MRI analysis using MOCART 64 or Henderson scores 65 and none used quantitative 3-dimensional analysis for structural assessments as described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4B), might significantly increase the difficulty of defect repair due to serious destruction of the local microenvironment and less mechanical support from surrounding cartilage3637. Second, severe surgical trauma caused by too many defects (4 defects) in both legs might have negatively influenced osteochondral regeneration and articular function recovery3738. Third, appropriate postoperative care and rehabilitation, which is difficult to guarantee in a large animal model, might impose another important negative factor394041.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Some authors have suggested that an upper limit of 7.5 cm 2 may exist and after this level, a poorer graft outcome may be observed. 27 , 44 A recent 5-year follow-up study has demon strated that factors such as graft size, duration of symptoms, preoperative Medical Outcomes Study 36-Item Short-Form Health Survey scores, and the postoperative course of weight-bearing rehabilitation are important factors contributing to positive 5-year clinical and radiological outcomes and overall patient satisfaction after MACI. 44 In our study, the mean defect size was 4.0 cm 2 , ranging 0.5–12 cm 2 .…”
Section: Discussionmentioning
confidence: 99%